Обзор систем принятия решений - Веселая, О. О. (ХНУРЭ, 2012)
The given work is devoted to analysis of decision support systems, their advantages and disadvantages. The purpose of the analysis is properly to an optimal model for the Intellectual Web application.
Keywords: analysis of decision support systems; Intellectual Web application; системы принятия решений